Map showing the field of operations of the Wilkins-Hearst Antarctic Expedition during the season of 1929-1930 / copyright . by the American Geographical Society of New York - American Geographical Society of New York (American Geographical Society of New York, 1930)
Relief shown by contours, hachures, and spot heights. Depths shown by soundings and isolines. "Elevations and soundings in meters." "The Geographical Review, V. XX, No. 3, 1930, Pl. III" -- upper right margin. Color 1:6,000,000